Production, Establishment and Characterisation of Monoclonal Antibody Against Breast Cancer Cell Line (Mcf-7) - Ong, Boo Kean (1995)
Ever since hybridoma technology was introduced by Kohler and Milstein in the 70's, numerous efforts have been undertaken to produce monoclonal antibodies (MAbs ) against mammary cancer cells. However, even to this day, all the MAbs produced still possess cross-reactivities toward other types of cancerous cells and also normal mammary cells. In this study, the breast cancer eel} line MCF-7 was used as an immunogen to raise MAb against mammary cancer cells. Fusion between lymphocytes sensitised with MCF-7 cell line and myeloma cells, SP2, was performed using 50% of polyethylene glycol (PEG). The hybridoma secreting MAb against MCF-7 cell line was selected using cell-ELISA technique. Limiting dilution of five times was performed to yield a stable hybridoma clone secreting the MAb.The selected clone, C2E7, which secreted MAb of the Igt-1 class and lamda light chains was chosen for further studies. MAb secreted by C2E7 was found to react with an antigenic determinant located in the cytoplasm of the MCF-7 cell line. Immunocytochemical studies showed that apart from the MCF-7 cell line, the anti genic determinant was also present in mammary cancer cell line of T47-D. Weak cross-reactivities were also observed against cell lines Panc-l and Ova-3. Immunohistochemical studies using the immunoperoxidase technique showed that staining occurred in the cytoplasmic region of all mammary lobular carcinoma and 90% of mammary ductal carcinoma examined. Staining was also found in 50% of mammary fibroadenoma cases studied. On the contrary, no staining of tissues was found in uterine leiomyoma, stomach showing intestinal metaplasia, cervical carcinoma, tonsillitis, neurofibroma, ductal papilloma of the breast and normal mammary tissues. Biochemical studies showed that the antigenic determinant on the MCF-7 cell line with reactivity towards MAb C2E7 was composed of endopeptide chain having arginine and lysine as the side chains, and possessed a specific conformational order which was disrupted when the determinant was electrophoresed on SDS-PAGE. Consequently, characterisation of the determinant using Western Blotting technique could not be performed. The hybridoma clone C2E7 was able to grow and proliferate in serum-free medium of EDRF supplemented with ITES. Purification technique using a combination of ammonium sulphate precipitation and gel filtration on Sepharose 6B enabled the separation of IgM from MAb secretion of C2E7 hybridomas cultured in serum-free medium.